Membangun Kesadaran Lingkungan Melalui Pos Membaca dan Bank Sampah “Di Desa Muara Bakti” - Montororing, Yuri Delano Regent; Utami, Puspita Dewi; Fadhilah, Adhan Husna; Kurniawan, Rangga Wirayuda; Fahrunnisa, Farah; Syaefuddin, Muhammad Dicky; Putri, Chika Amelia Alira; Ramdany, Sandy Wahyu; Aguchino, Banly; Fadilah, Muhammad Afnan (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
It is also hoped that the development of this reading park will raise public awareness of the importance of education and improve children's reading skills. With the help of a reading garden, children have wider access to reading materials and can improve their reading skills. In addition, reading parks can also be a way to raise public awareness of the importance of education and improve children's reading skills. Waste banks can also raise public awareness of the importance of good waste management. With the helpof waste bank volunteers, the community can improve the condition of a clean environment away from the disaster of waste accumulation. The method used to carry out this activity is the target method, which looks at how to strengthen the community to a clean village. This activity started with observations in the village of Jatimulya in the first week, followed by basic social activities.This action is expected to overcome the garbage problem, which is often caused by people carelessly discarding garbage.